2021
DOI: 10.1515/cls-2021-0016
|View full text |Cite
|
Sign up to set email alerts
|

Numerical estimation of the torsional stiffness characteristics on urban Shell Eco-Marathon (SEM) vehicle design

Abstract: Shell Eco-Marathon (SEM) is an international competition among university students that involves designing, building, and driving energy-efficient cars. The car frame is the most crucial aspect influencing the strength of the car. This research aims to obtain maximum torsional strength with variations in the material and thickness of the frame. Calculation and testing are done using the simulation method to obtain a strong car frame. This simulation method is calculated by a series of finite element analyses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In the design of automotive structures, the requirements commonly include stiffness requirements, i.e., bending stiffness and torsion stiffness, and safety factor under normal operating conditions (Ary et al, 2021;Li & Feng, 2020;Singh, 2010). Ary et al (2021) analyzed the shell eco-marathon structure with variations of materials and thicknesses under normal conditions, such as longitudinal and lateral loadings from braking and cornering. A suitable model was obtained by seeking the maximum torsional strength similar to the process used in designing an automobile chassis (Santa Rao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the design of automotive structures, the requirements commonly include stiffness requirements, i.e., bending stiffness and torsion stiffness, and safety factor under normal operating conditions (Ary et al, 2021;Li & Feng, 2020;Singh, 2010). Ary et al (2021) analyzed the shell eco-marathon structure with variations of materials and thicknesses under normal conditions, such as longitudinal and lateral loadings from braking and cornering. A suitable model was obtained by seeking the maximum torsional strength similar to the process used in designing an automobile chassis (Santa Rao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Research on torsional strength concluded that f the actor that exerts the most significant influence on torsional rigidity is the shear modulus and the material used [9]. The analyses of Abramyan (1951), Byrne and Carré (1962), and Marshall (1970, 1971 show that the torsional shear stress decreases through the wall thickness [10].…”
Section: Introductionmentioning
confidence: 99%
“…The Shell Group sponsors an international competition called the Shell Eco-marathon, which focuses on lowering vehicle fuel consumption and is competed in by university groups of enthusiastic automobile teachers and students all over the world [3][4][5][6][7][8]. This and similar events foster several automotive technology developments, including the demonstration of distinctive car designs [9][10][11] , energy management systems [12][13][14][15][16] , powertrain innovations [17][18][19][20], advanced use of materials and manufacturing methods [21,22], mechanical design [23][24][25][26][27] and the development of new 3D-printed automotive parts [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%